ANALISIS KUALITAS PRODUK SABUN CAIR DAN SABUN BATANG DI KALANGAN MAHASISWA - Umi Prasasti; Alfia Zahro; Syamsul Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of product quality of liquid soap and bar soap on purchasing decisions among students. This study used data collection techniques by surveying respondents through an online questionnaire with a sample size of 128 respondents for students with Likert scale measurements. Data analysis using validity test, reliability test, classical assumption test, multiple linear regression test and determination coefficient using quantitative descriptive approach. The results of this study concluded that liquid soap and bar soap have an influence on purchasing decisions. In this study, companies that have liquid soap and bar soap products are able to improve the quality of their products